2009
DOI: 10.1002/hep.23249
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of poly adenosine diphosphate-ribose polymerase decreases hepatocellular carcinoma growth by modulation of tumor-related gene expression

Abstract: H epatocellular carcinoma (HCC) is the fifth most common cancer in the world and the third most common cause of death from cancer in the world, accounting for an estimated 500,000 deaths annually. 1 The prognosis of HCC patients is generally very poor. Most studies have shown a 5-year survival rate of less than 5% in symptomatic patients. Because current therapies are rarely able to achieve complete tumor abla-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 36 publications
3
48
0
Order By: Relevance
“…Although the high normal pancreas activity may limit detection of the primary tumor, changes in pancreatic tumor uptake may still be helpful in determining treatment responses. In addition, PARP inhibitors also effectively treat hepatocellular carcinoma xenografts in mice (31), and human hepatocellular carcinoma has higher PARP expression than normal liver tissue (25) (25,28,29). The large proportion of parent compound remaining in the liver at 30 minutes was therefore most likely due to specific binding that prevented its metabolism.…”
Section: Molecular Imaging: Pet Of Poly (Adp-ribose)polymerase Activimentioning
confidence: 99%
“…Although the high normal pancreas activity may limit detection of the primary tumor, changes in pancreatic tumor uptake may still be helpful in determining treatment responses. In addition, PARP inhibitors also effectively treat hepatocellular carcinoma xenografts in mice (31), and human hepatocellular carcinoma has higher PARP expression than normal liver tissue (25) (25,28,29). The large proportion of parent compound remaining in the liver at 30 minutes was therefore most likely due to specific binding that prevented its metabolism.…”
Section: Molecular Imaging: Pet Of Poly (Adp-ribose)polymerase Activimentioning
confidence: 99%
“…This study suggests that targeting PARP-2 alone is an optional strategy to sensitize patients with HCC to chemotherapy and radiotherapy. Previous studies have reported increased expression of PARP-1 in a variety of tumors, including Ewing´s sarcomas [19], malignant lymphomas [20], colorectal cancer [21], HCC [8], breast, uterine, lung, and ovarian cancers [22]. PARP-2 is a member of the PARP family whose activity is stimulated by DNA strand interruptions targeting mainly proteins involved in chromatin structure and DNA metabolism [23].…”
Section: Discussionmentioning
confidence: 99%
“…Among the PARP members, PARP-1 and PARP-2 are the only known members whose activity is stimulated by DNA strand interruptions [7]. PARP-1 expression has been observed to be increased in a variety of tumors, including HCC [8]. In contrast, the expression of PARP-2 and its clinical significance as well as the therapeutic option of targeting PARP-2 have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, VEGF levels are significant in predicting disease progression from liver cirrhosis to hepatocellular carcinoma [134]. PARP-1 inhibition in hepatocellular carcinoma limits tumor growth and vasculogenesis by decreasing the levels of OPN, VEGF, interleukin-6, interleukin-1β, and tumor necrosis factor and by suppressing proliferation and NF-κB activation [135]. Combined gene therapy with interferon-αl and SG600-IL-24 (adenovirusmediated interleukin-24 expression) is an effective means for antitumor activity through down-regulating the levels of both OPN and VEGF [136].…”
Section: Liver and Pancreatic Cancersmentioning
confidence: 99%